Impact of a soccer match on the cardiac autonomic control of referees - Boullosa, D. A.; Abreu, L.; Tuimil, J. L.; Leicht, A. S. (European Journal of Applied Physiology, 2012)
The purpose of this study was to assess the effect of a soccer match on the cardiac autonomic control of heart rate (HR) in soccer referees. Sixteen Spanish regional and third division referees (11 males: 26 ± 7 years, 74.4 ± 4.1 kg, 178 ± 3 cm, Yo-Yo IR1 ~600-1,560 m; 5 females: 22 ± 3 years, 59.3 ± 4.8 kg, 158 ± 8 cm, Yo-Yo IR1 ~200-520 m) participated with 24-h HR recordings measured with a Polar RS800 during a rest and a match day. Autonomic control of HR was assessed from HR variability (HRV) analysis. Inclusion of a soccer match (92.5% spent at >75% maximum HR) reduced pre-match (12:00-17:00 hours; small to moderate), post-match (19:00-00:00 hours; moderate to almost perfect), and night-time (00:00-05:00 hours; small to moderate) HRV. Various moderate-to-large correlations were detected between resting HRV and the rest-to-match day difference in HRV. The rest-to-match day differences of low and high-frequency bands ratio (LF/HF) and HR in the post-match period were moderately correlated with time spent at different exercise intensities. Yo-Yo IR1 performance was highly correlated with jump capacity and peak lactate, but not with any HRV parameter. These results suggest that a greater resting HRV may allow referees to tolerate stresses during a match day with referees who spent more time at higher intensities during matches exhibiting a greater LF/HF increment in the post-match period. The relationship between match activities, [(V)\dot]\textO2max \dot{V}{\text{O}}_{2\max } and HR recovery kinetics in referees and team sport athletes of different competitive levels remains to be clarified.